Study of the antero-posterior position of the mental foramen in the Nepalese population using digital Panoramic Radiograph - Khanal, Pranaya; Chaudhary, Bikash; Twayana, Rajesh (Journal of Kathmandu Medical College, 2020)
Background: Mental foramen is an important landmark to be considered when operating in the anterior mandible. It is mandatory to identify the location of the foramen to prevent injury to mental nerve and subsequent paresthesia.Objectives: The objective of this study was to identify the position of the mental foramen in relation to the mandibular premolars and first molar in patients visiting Kathmandu Medical College, Department of Oral Surgery, Duwakot using the Orthopantomogram.Methodology: A total of 200 digital panoramic radiographs of 92 males and 108 females in the age range of 20-50 years were collected. Consequently, 184 mental foraminain males and 216 mental foraminain females were evaluated. The outline of the mandible along with canine, first premolar, second premolar, and first molar was traced. The mental foramen opening was also traced and the position wasevaluated in relation to the first, second premolars and first molar.Results: Out of 400 foramina, 217 (54.2%) were located between the first and second premolar, i.e. position 3. The second most commonlocationof 152 (38%) foramina was in line with the second premolar, i.e. position 4. Position 2, i.e. in line with the first premolar was seen in 4% and position 5, i.e. between the second premolar and first molar was seen in 3.5%. The left side (29.2%) had a higher occurrence of position 3 as compared to the right side (25%).Conclusion: The location of mental foramen should be identified in all surgeries involving the anterior mandible as this will help us prevent injury to the mental nerve.In our population, position 3 was the most common location of the mental foramen.